Three scleractinian coral diseases in Dominica, West Indies: distribution, infection patterns and contribution to coral tissue mortality - Borger, Jill L. (2003)
Coral diseases have been documented in many areas of the Caribbean, but studies in the eastern Caribbean region have been lacking. The prevalence, distribution patterns and contribution to the mortality of coral tissue by black band disease (BBD), white plague (WP) and dark spots disease (DSD) were examined at five reef sites along the west coast of Dominica. 185 of the 325 diseased colonies recorded between March and August 2000, in a survey area of 5884 m2, were WP. This disease contributed to 89% of the total 4.08 m2 of tissue mortality caused by diseases during the survey period. WP also affected the largest average tissue surface area (relative to colony size) per colony and exhibited the largest average tissue loss per infection when compared to BBD and DSD. The species most susceptible to WP and BBD in Dominica differed from most other described Caribbean locations with Siderastrea siderea being most susceptible. S. siderea was also the only species noted to be susceptible to DSD. Measurements of colony size revealed that each disease affected the larger colonies of some coral species. Comparisons between disease prevalence at each site and various physical parameters, including temperature, wave height, depth, and current patterns, did not exhibit significant correlations. The lack of a direct correlation between temperature and disease prevalence indicates that there are other seasonal factors contributing to the higher prevalence of diseases recorded during the summer months in Dominica. WP prevalence at each site was positively correlated to the relative species abundances of the species most susceptible to WP. This was the dominant factor in determining sitespecific disease densities of this disease and may therefore be a valuable predictive and management tool. There were no correlations between BBD or DSD and the relative abundances of susceptible species. The spatial distribution patterns of WP, BBD and DSD were clustered, which is a distribution pattern that suggests an infectious disease.